Effect of saffron supplementation on the glycemic outcomes in diabetes: a systematic review and meta-analysis - Liu, Jiaxin; Yang, Yang; Qi, Yun (Frontiers in Nutrition, 2024)
Aim: This meta-analysis was conducted to investigate the impact of saffron supplementation on the glycemic outcomes in patients with diabetes. Methods: Eight electronic databases were systematically searched from inception to March 31, 2023. RCTs of patients with diabetes receiving saffron compared with placebo which reported glycemic control outcomes were identified. WMD and 95% CIs were pooled using fixed-effects or random-effects models, depending on the significance of heterogeneity. Results: Out of the 837 citations screened, ten RCTs were included in the systematic review and metaanalysis. A total of 562 participants were enrolled, with 292 assigned to the intervention group and 270 to the control group. Saffron was administered at a dose of 5mg/day to 1g/day. Compared with placebo, saffron supplementation significantly reduced FPG (WMD = -8.42 mg/dl; 95% CI: -13.37, -3.47; P = 0.001) and HbA1c (WMD = -0.22%; 95% CI: -0.33, -0.10; P < 0.001). However, there was no significant effect on insulin levels, QUICKI and HOMA-IR. Conclusions: Saffron is effective for patients with diabetes in terms of FPG and HbA1c, therefore, it appears to be a promising adjuvant for the glycemic control of DM. However, the overall methodological quality of the identified studies is heterogeneous, limiting the interpretation of the benefit of saffron in diabetes. More long-term follow-up, well-designed and large-scale clinical trials are warranted to draw definitive conclusions.